Musicology as a meta-theory of musical meaning - Jabłoński, Maciej (Interdisciplinary Studies in Musicology, 2018)
The article is dedicated to the problem of musical meaning and its role in contemporary musicological and semiotic research and reflection on music and musical culture. Nowadays, semiotics of music became semiotics of becoming rather then semiotics of being, as it was earlier during the period of structuralism. What became the important is that the category of aisthesis is emphasized as well as the question of the experience, the aesthetic dimension of that experience and the subject itself. It is interesting to evaluate the postmodern thought as well, taking the question of its positive vs negative virtues, and — as a result — do not treat the postmodernism in negative way only (the aesthetic and the cognitive value of the sublime). To see the current changes of musicology one can speak not only about its relative autonomy and how to understand the limits of the discipline but also how to redefine the scope and core of musicology by treating to find more unconventional, closely ethic, perspectives and approaches (means: imagination, freedom of thought, openness to alternatives and to praise the uncertainty). If the musicology could be ready and able to join some efforts from other humanities: semiotics, history of arts, anthropology and cultural studies, the thesis of the musicology as a meta-theory of musical meaning could be valid.